Evolutionary Modifications Are Moderate in the Astroglial System of Actinopterygii as Revealed by GFAP Immunohistochemistry - Kálmán, Mihály; Matuz, Vanessza; Sebők, Olivér M.; Lőrincz, Dávid (Frontiers in Neuroanatomy, 2021)
The present paper is the first comparative study on the astroglia of several actinopterygian species at different phylogenetical positions, teleosts (16 species), and non-teleosts (3 species), based on the immunohistochemical staining of GFAP (glial fibrillary acidic protein), the characteristic cytoskeletal intermediary filament protein, and immunohistochemical marker of astroglia. The question was, how the astroglial architecture reflexes the high diversity of this largest vertebrate group. The actinopterygian telencephalon has a so-called ‘eversive’ development in contrast to the ‘evagination’ found in sarcopterygii (including tetrapods). Several brain parts either have no equivalents in tetrapod vertebrates (e.g., torus longitudinalis, lobus inferior, lobus nervi vagi), or have rather different shapes (e.g., the cerebellum). GFAP was visualized applying DAKO polyclonal anti-GFAP serum. The study was focused mainly on the telencephalon (eversion), tectum (visual orientation), and cerebellum (motor coordination) where the evolutionary changes were most expected, but the other areas were also investigated. The predominant astroglial elements were tanycytes (long, thin, fiber-like cells). In the teleost telencephala a ‘fan-shape’ re-arrangement of radial glia reflects the eversion. In bichir, starlet, and gar, in which the eversion is less pronounced, the ‘fan-shape’ re-arrangement did not form. In the tectum the radial glial processes were immunostained, but in Ostariophysi and Euteleostei it did not extend into their deep segments. In the cerebellum Bergmann-like glia was found in each group, including non-teleosts, except for Cyprinidae. The vagal lobe was uniquely enlarged and layered in Cyprininae, and had a corresponding layered astroglial system, which left almost free of GFAP the zones of sensory and motor neurons. In conclusion, despite the diversity and evolutionary alterations of Actinopterygii brains, the diversity of the astroglial architecture is moderate. In contrast to Chondrichthyes and Amniotes; in Actinopterygii true astrocytes (stellate-shaped extraependymal cells) did not appear during evolution, and the expansion of GFAP-free areas was limited.